Differential modulation of spinal nociceptive processing by aspirin-triggered resolvin D1 in rat pain models - Meesawatsom, Pongsatorn (2018)
Harnessing the actions of the resolvin pathways has the potential for the treatment of a wide-range of conditions associated with overt inflammatory signalling. Aspirin-triggered resolvin D1 (AT-RvD1) is a potent anti-inflammatory lipid derived from docosahexaenoic acid (DHA). In rodent, the biological effects of AT-RvD1 are mainly mediated by its specific G-protein coupled receptor, formyl peptide receptor 2 (ALX/FPR2). AT-RvD1 has been demonstrated potent anti-inflammatory and tissue resolution promoting (pro-resolving) activities in preclinical model of inflammatory diseases. Continuous peripheral activity of nociceptive fibres induces neuroinflammatory responses and alters the excitability neurones in both peripheral and central pain pathways. This thesis focused on spinal neuroinflammation which plays important roles in the sensitisation of nociceptive processing of the spinal dorsal horn neurones and contributes to the nociceptive hypersensitivity of the central pain pathway in acute and chronic pain. Since AT-RvD1 possess a potent anti-inflammatory activity, therefore, enhancing AT-RvD1 signalling in the spinal cord may attenuate the spinal nociceptive sensitisation and provide analgesia. AT-RvD1 also has robust antinociceptive effects in behavioural models of pain, however the potential underlying spinal neurophysiological mechanisms contributing to these inhibitory effects in vivo are yet to be determined. The purposes of this thesis were to investigate the differential effects of spinal AT-RvD1 on evoked responses of spinal neurones in vivo in well characterised pain models include carrageenan-induced acute inflammatory pain, monosodium iodoacetate (MIA)-induced OA pain and paclitaxel (PCX)-induced peripheral neuropathic pain and to investigate the alterations in the expression of spinal genes relevant to the resolvin system and neuroinflammation that may underlie the differential effects of AT-RvD1 among these pain models. Following model induction, pain behaviour was assessed and then rats were prepared for single unit extracellular recordings of dorsal horn wide dynamic range (WDR) neurones on the following day post carrageenan or day 28-32 post MIA or PCX induction. At the time-matched the spinal recording, ipsilateral dorsal quadrants of spinal cord form separate groups of rats were collected for gene expression quantification using TaqMan Low Density Arrays (TLDA). AT-RvD1 clearly demonstrated differential inhibition on evoked responses of WDR neurones in the pain models of interest. Low dose AT-RvD1 (15 ng/50ul) selectively produced a robust inhibition of electrical-evoked responses (Adelta-, C-fibre, post-discharge, input, wind-up) of WDR neurones in carrageenan rats but not in control rats. These effects were abolished by spinal pre-administration of a FPR2/ALX antagonist, butoxy carbonyl-Phe-Leu-Phe-Leu-Phe (BOC-2) (50 ug/50ul). In MIA rats, AT-RvD1 given at a high dose (150 ng/50ul) produced only mild inhibition of electrical evoked Adelta responses but not at a low dose (15 ng/50ul). AT-RvD1 (15 and 150 ng/50ul) had no significant effects on electrical evoked responses of PCX rat WDR neurones. Interestingly, AT-RvD1 produced a dose dependent and selective inhibition of low intensity mechanical evoked responses PCX rats whereas it had no effects in control rats. At high dose (150 ng/50ul), the magnitude of inhibition of 8g mechanical evoked responses was comparable to morphine (1 ug/50ul) applied at the end of the experiments. AT-RvD1 produced a dose dependent inhibition of acetone-evoked responses in PCX rats, however WDR neurones in the control rats were also inhibited to a similar degree. TLDA revealed the distinct alteration of resolvin genes in spinal cord underpinning the differential inhibition of AT-TvD1. Upregulated 5-lipoxygenase activating protein (FLAP) gene, encoding protein determining endogenous resolvin synthesis, in carrageenan and PCX rats may underlie the robust inhibition of AT-RvD1 on WDR neurones in these two models. The minimal effects AT-RvD1 of MIA rats were associated with upregulated 15-hydroxyprostaglandin dehydrogenase (15-HPGD) gene, encoding a major enzyme responsible for D-series resolvin inactivation. Data presented in this thesis provide for the first time the differential inhibition of AT-RvD1 on spinal nociceptive processing in different types of pain and the evidence of heterogeneous spinal alterations of the resolvin signalling potentially underlie such inhibition. This thesis strongly supports further investigation of AT-RvD1 as a novel analgesic. Another part of this thesis demonstrated changes in the responses of spinal WDR neurones in PCX rats. Spinal WDR neurones from PCX rats displayed characteristics representing pain sensitisation including: reduced the thresholds for Abeta and C-fibre responses; increased proportion of neurones exhibiting spontaneous activity, acetone responsiveness and post-discharge following low intensity mechanical stimuli and a more convergence in stimulus processing. A remarkable upregulation of multiple genes in proinflammatory signallings, toll-liked receptor 4 (Tlr4), interleukin-1 (Nlrp1a) and tumour necrosis factor-alpha receptors (Tnfrsf1a and Tnfrsf1b) and chemokines (Cxcl6, Cxcr1, Cxcr5, Ccr1, Cx3cr1), was found in the spinal cord of PCX rats. This suggests that a high inflammatory component in the spinal cord could contribute to the changes in the responses of spinal WDR neurones in the PCX rats. This thesis supports further investigation of targeting neuroinflammation as a promising approach for the treatment of PCX-induced neuropathic pain.